Invitations eaudiobook - Nascosta, C.M (Monster Bait Romance, 2024)
Lurielle didn't dream of her wedding as a little girl. Now the orc of her dreams is telling her he's going to build her a bridal fire they can see from space. It doesn't help that the engagement has gripped the entire town, and as Khash catches the fever, all Lurielle wants to do is elope. At least she can count on her friends to help her . . . at least, she thinks she can. Ris isn't sure how she managed to get so lucky. Ainsley is everything she wants, and she's ready to be the best bridesmaid. But when his support system vanishes, the Ainsley she loves seems to disappear overnight. In his place is an orc who wants more than Ris thinks she's prepared to give. It's hard to focus on someone else's happily ever after when her own is going through growing pains. Thank the stars Silva is there to help. For as long as she could remember, Silva daydreamed about her wedding, and she's ready for the future—Silva and the orc of her dreams living their best life, because nothing is going to stop her from getting what she wants. Nothing, except for the truth Tate hid from her. It's hard to plan someone else's happily ever after when you don't believe in them anymore. Contains mature themes.